Leveraging Service Sector Growth in the Philippines - Raja Mikael Mitra (Asian Development Bank (ADB), 2013)
The Philippines is often referred to as a country from which export of services rather than manufactured goods is the principal engine for economic growth, as the share of the service sector in gross domestic product has exceeded that of the industry sector since the mid-1980s. Three major opportunities for leveraging service sector growth stands out. One is expanding the scale and scope of the export and domestic markets for information technology-business process outsourcing and other modern services in urban areas. Second is expanding tourism to foster economic development across social groups and regions including poor and remote rural areas. Third is enhancing the domestic prospects for Filipino technical, managerial, and entrepreneurial talent so they will work in the Philippines rather than overseas. To take advantage of those opportunities, there is a need for concerted efforts to improve infrastructure; logistics; broadband connections; the power supply; and education, healthcare, financial, legal, and public administration services and more generally the overall business environment for foreign investors and local entrepreneurs.
hdl:11540/2296
Keywords: F22; L80; O14; 330; services; growth; Philippines; Asia; business process outsourcing; information technology; migration; diaspora; tourism; innovation; knowledge economy